Sikap Etnosentrisme Memoderasi Pengaruh Product Knowledge, Citra Merek dan Gaya Hidup terhadap Keputusan Pembelian Produk UMKM - Nurcaya, I Nyoman (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 14 Nomor 1 Tahun 2020DO - 10.24843/MATRIK:JMBK.2020.v14.i01.p06, 2020)
Micro, Small and Medium Enterprises (MSMEs) have an important role in the development and economic growth of Bali. One of the MSMEs that still exists and survives in the Province of Bali is Endek fabric. Increasingly intense competition demands endek MSMEs to make competitive competitive strategies.This study aims to explain consumer ethnocentrism attitudes capable of moderating product knowledge, brand image and lifestyle towards consumer decisions to buy endek Bali products. To achieve these objectives 95 respondents were spread across Bali Province and will be taken by purposive sampling with questionnaires as the method of data collection. Data is processed by Partial Least Square (PLS) analysis tools.The results of the analysis show that product knowledge, brand image and ethnocentrism have a significant effect on the purchase of Bali SME endek fabric, while lifestyle variables do not prove to significantly influence purchasing decisions. Ethnocentrism variables reinforce the influence of product knowledge and brand image on purchasing decisions but weaken the influence of lifestyle on purchasing decisions.